2013
DOI: 10.1155/2013/635214
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum and Urinal Copper and Zinc in Chinese Northeast Population with the Prediabetes or Diabetes with and without Complications

Abstract: This study investigated the association of copper and zinc levels in the serum or urine of patients living in northeast China, with either prediabetes or diabetes. From January 2010 to October 2011, patients with type 1 diabetes (T1D, n = 25), type 2 diabetes (T2D, n = 137), impaired fasting glucose (IFG, n = 12) or impaired glucose tolerance (IGT, n = 15), and age/gender matched controls (n = 50) were enrolled. In the T2D group, there were 24 patients with nephropathy, 34 with retinopathy, and 50 with periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 39 publications
(42 reference statements)
7
48
0
Order By: Relevance
“…Vashum et al [11] observed a significant association of zinc levels with insulin sensitivity in pre-diabetes even though no significant difference in serum levels was found in their study between pre-diabetes, diabetes and controls. Xu et al [24] also observed a deficiency similar to the present study in pre-diabetes. This spectrum of observations from different studies conducted in different countries could be attributed to the population profiles differing substantially in dietary composition and geographical distribution [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Vashum et al [11] observed a significant association of zinc levels with insulin sensitivity in pre-diabetes even though no significant difference in serum levels was found in their study between pre-diabetes, diabetes and controls. Xu et al [24] also observed a deficiency similar to the present study in pre-diabetes. This spectrum of observations from different studies conducted in different countries could be attributed to the population profiles differing substantially in dietary composition and geographical distribution [24].…”
Section: Discussionsupporting
confidence: 91%
“…Xu et al [24] also observed a deficiency similar to the present study in pre-diabetes. This spectrum of observations from different studies conducted in different countries could be attributed to the population profiles differing substantially in dietary composition and geographical distribution [24].…”
Section: Discussionsupporting
confidence: 91%
“…In general, concentrations of Cu were similar between diabetics and controls (27)(28)(29). However, the high levels of Cu found in our patients have been reported by other series (30). This could be, in part, explained by the decrease in Cu affinity to ceruloplasmin because of its glycosylation in the diabetic patients (31).…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings were found with zinc levels and insulin, and HOMA-IR levels. Zinc is also a cofactor for insulin biosynthesis and storage in pancreatic β cells [33]. Zinc deficiency may induce abnormal insulin metabolism.…”
Section: Discussionmentioning
confidence: 99%